A framework for understanding sexual violence: Incentive-motivation and hierarchical control. (May 2017) - Toates, Frederick; Smid, Wineke; van den Berg, Jan Willem
Abstract: The article applies an incentive-motivation model to sexual violence. It suggests that insights can be gained by looking at the biopsychological processes that underlie 'conventional behavior'. It argues that sexual violence, as in rape, arises from a fusion between (i) sexual motivation and (ii) sensation-seeking and varying strengths of dominance/aggression motivations. The excitatory part of the motivational system is rooted in brain dopamine and sexual violence is expressed in behavior when excitation exceeds inhibition. The assumptions are framed within the principle of the hierarchical control of behavior. The incentive-motivation and hierarchical framework can yield insights into such phenomena as planning and impulsivity, future discounting, habituation and escalation, violence as addiction, the role of fetishes, sexual fantasy, stress, drugs and brain development. Highlights: Incentive motivation theory gives profound insight into sexual violence. The brain processes underlying sexual violence are organized as a hierarchy. Sexual desire and the desire for dominance/aggression can merge in their effects. Dopamine underlies sexual desire and dominance, giving a basis to confluence theory. The model can illuminate a range of phenomena such as sexual homicide.